2022
DOI: 10.1111/1755-0998.13587
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐scale reference genome assembly of yellow mangrove (Bruguiera parviflora) reveals a whole genome duplication event associated with the Rhizophoraceae lineage

Abstract: Mangrove forest ecosystems support a diverse flora and fauna of marine and terrestrial species and have important direct and indirect economic, ecological and social values to mankind. Yellow mangrove (Bruguiera parviflora) belongs to the Rhizophoraceae family and is widely distributed in the intertidal zones along sheltered coastal areas in tropical latitudes. Here, we present a high‐quality, chromosome‐level assembly of the B. parviflora genome. We employed the 10x Genomics linked‐read technology to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 92 publications
2
20
1
Order By: Relevance
“…Most of the retrotransposons were classified as long terminal repeats (39.76 Mb), which could further be categorized into Copia -like (15.60 Mb) and Gypsy -like (19.07 Mb) elements ( supplementary table 4, Supplementary Material online). The percentage of the B. sexangula assembly containing repetitive elements (38.2%) was higher than that observed in the K. obovata (24%) ( Hu et al 2020 ), B. parviflora (26%) ( Pootakham, Sonthirod, Naktang, Kongkachana, Sangsrakru, et al 2022 ) and R. apiculata (29%) ( Xu et al 2017 ) genomes but comparable to the figure reported for the Populus trichocarpa genome (40%) ( Zhou and Xu 2009 ).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Most of the retrotransposons were classified as long terminal repeats (39.76 Mb), which could further be categorized into Copia -like (15.60 Mb) and Gypsy -like (19.07 Mb) elements ( supplementary table 4, Supplementary Material online). The percentage of the B. sexangula assembly containing repetitive elements (38.2%) was higher than that observed in the K. obovata (24%) ( Hu et al 2020 ), B. parviflora (26%) ( Pootakham, Sonthirod, Naktang, Kongkachana, Sangsrakru, et al 2022 ) and R. apiculata (29%) ( Xu et al 2017 ) genomes but comparable to the figure reported for the Populus trichocarpa genome (40%) ( Zhou and Xu 2009 ).…”
Section: Resultssupporting
confidence: 56%
“…The preliminary assembly generated from the linked-read data was 263,981,354 bases with an N50 contig length of 1,414,200 bases ( table 1 ). This assembly was further scaffolded with RagTag using a chromosome-scale assembly of a closely related mangrove species, B. parviflora ( Pootakham, Sonthirod, Naktang, Kongkachana, Sangsrakru, et al 2022 ), as a reference. The final assembly contained 260,518,658 bases in 20,644 scaffolds with an N50 length of 11,020,310 bases ( fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations